The One Health Clinic: Care for Young Adults and Companion Animals Experiencing Homelessness - Natalie Rejto; Vickie Ramirez; Hannah T. Fenelon; Michael Xie; Katie Kuehl; Anina Terry; Alice H. Tin; Erin Tabor; Kate Schneier; Andrew Nee; Amanda Richer; Peter Rabinowitz; et al. (Journal of Primary Care & Community Health)
Introduction/Objective: This study evaluates 4 years of data from the Seattle One Health Clinic (OHC), a novel model for clinical care which integrates human and animal health care services for youth and young adults experiencing homelessness (YPEH) and their pets. Methods: We analyzed deidentified data from standardized OHC visit forms, electronic medical records, and veterinary records from 2019 to 2022. We assessed the overlaps between human and animal healthcare provided and the impact of environmental stressors on both human and animal patients. Results: Over 50% of all human clients established healthcare for the first time in 2 years, with 85% attending one or more follow-up appointments with non-emergency healthcare services within 2 years following their initial OHC appointment. All animals received care during their visit. Needs addressed at the human-animal interface included zoonotic infections, animal allergies, and mental/behavioral health. The most common client-pet reported environmental concerns were food insecurity, heat, and cold. Conclusion: Our results suggest integrated human and animal healthcare is a feasible and acceptable model of care for YPEH to access acute and preventative care at the human-animal-environmental interface. This approach holds promise for increasing health-seeking behaviors, and engagement in preventative, therapeutic, and follow-up care.